TELAAH AWAL ATAS TAFSIR JĀMI’ AL-BAYĀN MIN KHULĀṢAH SUWAR AL-QUR`ĀN KARYA KH. MUHAMMAD BIN SULAIMAN (1329-1412 H/ 1911-1991 M) - Arifin, Moch. (STAI AL-ANWAR SARANG, 2016)
Jāmi’ Al-Bayān min Khulāṣah Suwar Al-Qur`ān by KH. Muhammad bin Sulaiman (1329 - 1412 H) Solo, Central Java, is one piece of exegesis work among the others in Indonesia which is not well-known by public. This study is aimed at introducing this exegesis work, through some topics raised here, namely the background or history of the writing, the exegesis methods, sources, systematics, and the contribution of Jāmi’ Al-Bayān min Khulāṣah Suwar Al-Qur'an in Indonesia. This study is relevant as to bring this work to the surface to be known by the public. This study concludes that Jāmi’ Al-Bayān min Khulāṣah Suwar Al-Qur'an is considered unique. The style of exegesis which KH. Muhammad initiated is in the form of concise commentary points as global essence of the verses. Furthermore, what makes this work of exegesis interesting is the sources of exegesis which are always present in the end of every commentary. To KH. Sulaiman, sanad is prioritized in keeping the orthodoxy of the Qur'anic exegesis.